2001
DOI: 10.1108/09576060110361582
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ISO 9000 registration on European firms: a case analysis

Abstract: ISO 9000 certification serves as an entré into the global marketplace. European firms have been the most prolific in obtaining ISO 9000 certification. The certification experiences of 11 European firms are described. On‐site interviews and questionnaires were used to identify: the obstacles encountered during the implementation effort; the impacts certification had on operational factors; and the ISO 9000 elements requiring the greatest resources. Results suggest that firms of different sizes, in different ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
6

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 10 publications
(15 reference statements)
0
27
0
6
Order By: Relevance
“…Finally, the third group shows that companies are based on both internal and external factors when deciding to begin the process that allows them to obtain the certification (Beattie & Sohal, 1999;Carlsson & Carlsson, 1996;Corbett, Luca, & Pan, 2003;Escanciano, Fernández, & Vázquez, 2001;Fuentes, Benavent, Moreno, Cruz, & del Val, 2000;Huarng, Horng, & Chen, 1999;Lee & Palmer, 1999;Magd & Curry, 2003;Prajogo, 2009;Mariotti, Kadasah, & Abdulghaffar, 2014;Mathews, Ueno, Periera, Silva, Kekal, & Repka, 2001;Sampaio, Saraiva, & Rodrigues, 2009;Sun & Cheng, 2002;Taylor, 1995;Tsiotras & Gotzamani, 1996;Withers & Ebrahimpour, 1996;Withers & Ebrahimpour, 2001). The analysis of these 4…”
Section: Internal Reasonsmentioning
confidence: 97%
“…Finally, the third group shows that companies are based on both internal and external factors when deciding to begin the process that allows them to obtain the certification (Beattie & Sohal, 1999;Carlsson & Carlsson, 1996;Corbett, Luca, & Pan, 2003;Escanciano, Fernández, & Vázquez, 2001;Fuentes, Benavent, Moreno, Cruz, & del Val, 2000;Huarng, Horng, & Chen, 1999;Lee & Palmer, 1999;Magd & Curry, 2003;Prajogo, 2009;Mariotti, Kadasah, & Abdulghaffar, 2014;Mathews, Ueno, Periera, Silva, Kekal, & Repka, 2001;Sampaio, Saraiva, & Rodrigues, 2009;Sun & Cheng, 2002;Taylor, 1995;Tsiotras & Gotzamani, 1996;Withers & Ebrahimpour, 1996;Withers & Ebrahimpour, 2001). The analysis of these 4…”
Section: Internal Reasonsmentioning
confidence: 97%
“…Since ISO 9000 series of standards first emerged in 1987, many authors found that ISO offered a reasonable first step toward implementing quality (Bradley, 1994;Claver et al, 2002;Escanciano et al, 2001;Gotzamani and Tsiotras, 2002;Skrabec, 1999;Stephens, 1997;Sun, 2000;Taylor, 1995;Tummala and Tang, 1996;Withers and Ebrahimpour, 2001;Yusof and Aspinwall, 2000). This initial version of ISO addressed quality issues in categories such as quality policy, quality documentation and quality planning.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…Cer tif i ca tion is seen as a way for or gani sations to achieve com pet i tive ness in the mar ket places [Najmi and Kehoe, 2001;Rao et al, 1997], con tin u ous im prove ment, profit im prove ment, market ing ben e fits, and a better run or gani sa tion [Singels et al, 2001;Yung, 1997;Prabhu et al, 2000;Beat tie and Sohal, 1999;Wiele et al, 2005;Dimara et al, 2004;Aarts and Vos, 2001]. More over, other re search ers [Arauz and Suzuki, 2004;Heras et al, 2001;With ers and Ebrahimpour, 2001] con cluded that the in crease in per ceived qual ity as a re sult of ISO imple men ta tion should re sults in new cus tom ers, in creased sales and re duced op er at ing costs. How ever, the im ple men ta tion and the im pact of ISO standards can vary from or gani sa tion to or gani sa tion and from coun try to country.…”
Section: Iso Cer Tif I Ca Tion: An Over Viewmentioning
confidence: 99%